Identification of a robust promoter in mouse and human hepatocytes by in vivo biopanning of a barcoded AAV library - Becker, Jonas; Domenger, Claire; Choksi, Pervinder; Krämer, Chiara; Baumgartl, Conradin; Maiakovska, Olena; Kim, Jae-Jun; Weinmann, Jonas; Huber, Georg; Schmidt, Florian; Thirion, Christian; Müller, Oliver J.; et al. (Molecular therapy, 2025)
Recombinant adeno-associated viruses (AAVs) are leading vectors for in vivo human gene therapy. An integral vector element is promoters, which control transgene expression in either a ubiquitous or cell-type-selective manner. Identifying optimal capsid-promoter combinations is challenging, especially when considering on- versus off-target expression. Here, we report a pipeline for in vivo promoter biopanning in AAV building on our AAV capsid barcoding technology and illustrate its potential by screening 53 promoters in 16 murine tissues using an AAV9 vector. Surprisingly, the 2.2-kb human glial fibrillary acidic protein (GFAP) promoter was the top hit in the liver, where it outperformed robust benchmarks such as the human α-1-antitrypsin promoter or the clinically used liver-specific promoter 1 (LP1). Analysis of hepatic cell populations revealed preferred GFAP promoter activity in hepatocytes. Notably, the GFAP promoter also surpassed the LP1 and cytomegalovirus promoters in human hepatocytes engrafted in an immune-deficient mouse. These findings establish the GFAP promoter as an exciting alternative for research and clinical applications requiring efficient and specific transgene expression in hepatocytes. Our pipeline expands the arsenal of technologies for high-throughput in vivo screening of viral vector components and is compatible with capsid barcoding, facilitating the combinatorial interrogation of complex AAV libraries.
Online verfügbar: 21. April 2025, Artikelversion: 6. August 2025
Gesehen am 20.01.2026